Dispositivo óptico para medida em tempo real da birrefringência de polímeros durante a extrusão - Soares, Kinglston (2010)
The main objectives of this project were the development and application of an optical device to measure in real time the flow induced birefringence during the polymer extrusion. The linearly polarized light intensity transmitted through the molten polymer flowing in the slit-die is converted into birefringence via its relation with the optical path difference (OPD). The optical device was calibrated on the bench with the use of polycarbonate sheets with known OPD values. In addition, a methodology was developed to deduct the contribution of the strain birefringence of the transparent glass windows of the Rheophotometer. As flow polymers three polystyrene grades were showsen because of their high flow birefringence. The polymer flow temperature and the slit-die inlet pressure were assessed analyzing their effect in the polymer flow birefringence during extrusion. The results show a good relation with the rheological behavior of the polymer. Increasing the melt temperature there is a reduction in the inlet pressure of the slit-die lowering the birefringence flow values due to the increase of the random molecular motions. Both reduce the intensity of secondary forces that could contribute to the orientation. The greater the feeding rate the higher the chain orientation raising the birefringence values. As polymers are pseudoplastic increases in the shear stress leads to chain orientation in the flow direction. At a constant inlet pressure in the slit-die the higher the molecular weight of the polymer the higher the chain orientation producing higher flow birefringence values. These results do show the good quantitative performance of the optical device developed.